New Technologies in 3D Mapping - Atoyan, Ruben; German, Anna (Bulletin of Geography. Physical Geography Series, 2017)
Among cartographic works three-dimensional panorama should be marked out the special kind of maps, which are characterized with visual modes of presentation of objects in space. The main principles of creation both of hand-painted and automated maps by means of the program of vector and raster graphics (CorelDRAW and Adobe Photoshop) are considered in the paper. The use of modern information technologies has several advantages over traditional mapping.